Screening for gestational diabetes mellitus by two step method and the neonatal outcome - Srinivasan, Suguna; Palanisamy, Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: As Indian women has increased risk of developing GDM, screening for GDM is essential for early diagnosis and treatment and hence to reduce the adverse neonatal outcomes. Methods: The antenatal women are screened for GDM by administering 50g GCT and the screening test value of >130mg/dl measured at 1 hours were considered screening test positive and subjected to standard 2 hour 75gm OGTT and the neonatal outcome were observed in relation to neonatal birth weight, Apgar, and the occurrence of complications like hypoglycemia, hypocalcemia, hyperbilirubenemia. Results: The average neonatal birth weight in the study population was 3kg. The women with GDM who required diet alone had average neonatal birth weight of 2.9kgs and the GDM women who were on diet and insulin therapy had average neonatal birth weight of 3.4kg. There was increased incidence of hyperbilirubinemia 33.3% .There was only 1 preterm birth. Conclusions: There is association with neonatal Complications like hyperbilirubenemia and hypoglycemia with women who had screening positive for GDM.